Studies on the RC Beam Strengthened by Using the Exterior-Wrapping U-Shaped Steel Plate and Its Application - Chunli Zhou; Jinkun Sun; Zhaorong Zeng; Jie Liu (Advances in Civil Engineering)
Based on practical frame structures, constructional methods of the reinforced concrete (RC) frame beam strengthened by using an exterior-wrapping U-shaped steel plate are introduced. With reference to the code for design of strengthening concrete structure, the bearing capacity formula of the RC frame beams strengthened by using the exterior-wrapping U-shaped steel plate is briefly derived. After that, the finite element analysis of the frame beam before and after the reinforcement of the engineering example is carried out through ABAQUS software, and the results of the analysis of the bearing capacity are compared with the calculation results of the theoretical formula. At the same time, through comparing and analysing the U-shaped steel plate strengthening method and the “angle steel + batten plate” strengthening method, the result that the RC beam strengthened by using the exterior-wrapping U-shaped steel plate has better mechanical performance is drawn. Finally, the application of the exterior-wrapping U-shaped steel plate strengthening method is rationally suggested.